Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effects of amount of lactose in milk replacer on gastrointestinal function of dairy calves - R. Fukumori; T. Nakayama; M. Hirose; I. Norimura; K. Izumi; K. Shimada; H. Mineo; M.A. Steele; S. Gondaira; H. Higuchi; T. Watanabe; H. Ueda; et al. (Animal Feed Science and Technology, 2025)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

New cadinene-sesquiterpene from Chromolaena laevigata (lam.) R. M. King & H. Rob (Asteraceae) aerial parts and biological activities - Josiane A. Monteiro de Oliveira; Darlon Irineu Bernardi; Rodolfo Bento Balbinot; Márcia Regina Pereira Cabral; Érica Benassi Zanqueta; Eliana H. Endo; Benedito Prado Dias Filho; Tania Ueda Nakamura; Mariana Cecchetto Figueiredo; Ana Lucia Tasca Gois Ruiz; Mary Ann Foglio; Marta Regina Barrotto do Carmo; et al. (Natural Product Research, 2021)

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Effects of Transcranial Direct Current Stimulation of the Posterior Parietal Cortex on the Control of Visual Attention - Y. Hirakawa; K. Takeda; S. Tanabe; S. Koyama; T. Ueda; K Morishima; M. Iwai; S. Kuno; I. Motoya; H. Sakurai; Y. Kanada (Neurophysiology, 2019)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

The behavioural homing response of adult chum salmon Oncorhynchus keta to amino‐acid profiles - E. Y. Chen; J. B. K. Leonard; H. Ueda (Journal of Fish Biology, 2017)
Adult chum salmon Oncorhynchus keta homing behaviour in a two‐choice test tank (Y‐maze) was monitored using a passive integrated transponder (PIT)‐tag system in response to river‐specific dissolved free amino‐acid ( DFAA ) profiles and revealed that the majority of O. keta showed a preference for artificial natal‐stream water and tended to stay in this maze arm for a longer period; natal‐stream water was chosen over a nearby tributary's water, but not when the O. keta were presented with a non‐tributary water. The results demonstrate the ability of O. keta to discriminate artificial stream waters containing natural levels of DFAA .

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Enhanced loading regimen of teicoplanin is necessary to achieve therapeutic pharmacokinetics levels for the improvement of clinical outcomes in patients with renal dysfunction - T. Ueda; Y. Takesue; K. Nakajima; K. Ichiki; A. Doita; Y. Wada; T. Tsuchida; Y. Takahashi; M. Ishihara; H. Ikeuchi; M. Uchino; T. Kimura (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Characterization of a new anulavirus isolated from Amazon lily plants - S. Fuji; M. Kikuchi; S. Ueda; T. Toda; H. Furuya; F. Fukumoto; K. Hanada (Archives of Virology, 2013)

Physiological mechanisms of imprinting and homing migration in Pacific salmon Oncorhynchus spp. - H. Ueda (Journal of Fish Biology, 2012)
After several years of feeding at sea, salmonids have an amazing ability to migrate long distances from the open ocean to their natal stream to spawn. Three different research approaches from behavioural to molecular biological studies have been used to elucidate the physiological mechanisms underpinning salmonid imprinting and homing migration. The study was based on four anadromous Pacific salmon Oncorhynchus spp., pink salmon Oncorhynchus gorbuscha , chum salmon Oncorhynchus keta , sockeye salmon Oncorhynchus nerka and masu salmon Oncorhynchus masou , migrating from the North Pacific Ocean to the coast of Hokkaido, Japan, as well as lacustrine O. nerka and O. masou in Lake Toya, Hokkaido, where the lake serves as the model oceanic system. Behavioural studies using biotelemetry techniques showed swimming profiles from the Bering Sea to the coast of Hokkaido in O. keta as well as homing behaviours of lacustrine O. nerka and O. masou in Lake Toya. Endocrinological studies on hormone profiles in the brain–pituitary–gonad axis of O. keta , and lacustrine O. nerka identified the hormonal changes during homing migration. Neurophysiological studies revealed crucial roles of olfactory functions on imprinting and homing during downstream and upstream migration, respectively. These findings are discussed in relation to the physiological mechanisms of imprinting and homing migration in anadromous and lacustrine salmonids.

Sources of Information that Promote Breast and Cervical Cancer Knowledge and Screening Among Native Hawaiians in Southern California - Jacqueline H. Tran; Michele Mouttapa; Travers Y. Ichinose; Jane Ka’ala Pang; Dawn Ueda; Sora Park Tanjasiri (Journal of Cancer Education, 2010)

The orf virus inhibitor of apoptosis functions in a Bcl-2-like manner, binding and neutralizing a set of BH3-only proteins and active Bax - Dana Westphal; Elizabeth C. Ledgerwood; Joel D. A. Tyndall; Merilyn H. Hibma; Norihito Ueda; Stephen B. Fleming; Andrew A. Mercer (Apoptosis, 2009)

Molecular biological research on olfactory chemoreception in fishes - H. Hino; N. G. Miles; H. Bandoh; H. Ueda (Journal of Fish Biology, 2009)
This review describes recent molecular biological research on olfactory chemoreception in fishes. The recent rapid development of molecular biological techniques has provided new valuable information on the main and vomeronasal olfactory receptor (OR) genes, the axonal projection from ciliated, microvillous and crypt‐olfactory receptor cells to the olfactory bulb, properties of odorant substances and olfactory imprinting and homing in salmon. Many important questions, however, remain unanswered on functional differences among OR genes, on ligand binding to each OR and on the molecular biological mechanisms underlying olfactory imprinting and homing in salmon. Olfactory chemoreception is believed to be the oldest sensory cue for both animal survival and adaptation to various different environments. Further intensive molecular biological research on olfactory memory formation and remembrance should be carried out to clarify the fundamental process of olfactory chemoreception in fishes.

Effects of external and surgically implanted dummy radio transmitters on mortality, swimming performance and physiological status of juvenile masu salmon Oncorhynchus masou - Y. Makiguchi; H. Ueda (Journal of Fish Biology, 2009)
The effects of external and surgically implanted radio transmitters on juvenile masu salmon Oncorhynchus masou were examined. External attachment of transmitters significantly decreased the survival of fish and caused a decreased critical swimming speed compared with surgical implantation. Although plasma cortisol, plasma glucose and haematocrit values did not differ significantly among groups, it appeared that the most suitable transmitter attachment method for juvenile O. masou may be surgical implantation.

Migratory behaviour of adult chum salmon, Oncorhynchus keta , in a reconstructed reach of the Shibetsu River, Japan - Y. MAKIGUCHI; H. NII; K. NAKAO; H. UEDA (Fisheries Management and Ecology, 2008)
During 2004–2006, 30 adult chum salmon, Oncorhynchus keta (Walbaum), were tagged with electromyogram (EMG) transmitters and depth/temperature loggers and tracked along both the channelised and reconstructed segments of the Shibetsu River, Japan to assess the effects of the river re‐meandering construction on upstream migration. Holding time of chum salmon in the reconstructed segment was longer than in the channelised segment. Further, greater diversity of physical condition in water velocity was observed in the reconstructed segment in 2005. Swimming speeds decreased during holding and often exceeded the critical swimming speed ( U crit ). It appears that the physical characteristics developed in the reconstructed segment may be suitable for holding of chum salmon. Further, swimming speed exceeding U crit prior to holding may be exhaustive so holding behaviour may be important for muscle recovery as well as for efficient swimming to reduce the energetic cost during upstream migration.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Upstream migration of adult chum and pink salmon in the Shibetsu River - Y. Makiguchi; H. Nii; K. Nakao; H. Ueda (Hydrobiologia, 2007)

Relationship between eyed‐egg percentage and levels of cortisol and thyroid hormone in masu salmon Oncorhynchus masou - M. Mingist; T. Kitani; N. Koide; H. Ueda (Journal of Fish Biology, 2007)
A possible cause of the low eyed‐egg percentage that afflicts pond‐reared masu salmon Oncorhynchus masou at a fish hatchery (Kumaishi Fish Hatchery, Hokkaido, Japan) was investigated. Serum cortisol levels of masu salmon during the spawning period were compared between individuals from Kumaishi and those from another station (Mori). Cortisol, thyroxine (T 4 ) and triiodothyronine (T 3 ) hormones were also measured in eyed eggs and their levels were compared to the eyed‐egg percentage. Serum cortisol levels were significantly higher at Kumaishi than at Mori in May and July of the breeding season. At the Kumaishi station, there was a linear positive relationship between serum cortisol and fertilized‐egg cortisol levels of female masu salmon. As cortisol levels in both ovulating females and eyed eggs increased, the eyed‐egg percentage decreased, indicating a highly significant negative relationship between cortisol levels and eyed‐egg percentage. In contrast, as T 3 and T 4 levels in eyed eggs increased, the eyed‐egg percentage increased. The strong positive correlation between high cortisol levels in serum and in eyed eggs at Kumaishi indicates that the frequently higher cortisol levels may have caused the lowering of the eyed‐egg percentage.

Bovine and water buffalo Mx2 genes: polymorphism and antiviral activity - H. A. E. Babiker; Y. Nakatsu; K. Yamada; A. Yoneda; A. Takada; J. Ueda; H. Hata; T. Watanabe (Immunogenetics, 2006)

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

Complete nucleotide sequence of the genomic RNA of an Amami-O-shima strain of East Asian Passiflora potyvirus - H. Iwai; R. Terahara; Y. Yamashita; S. Ueda; M. Nakamura (Archives of Virology, 2006)

Synchronous recruitment and growth pattern of planktonic larvae of the amphioxus Branchiostoma belcheri in the Seto Inland Sea, Japan - H. Ueda; H. Kamakura (Marine Biology, 2006)

Roles of Aquaporin-3 Water Channels in Volume-Regulatory Water Flow in a Human Epithelial Cell Line - H. Kida; T. Miyoshi; K. Manabe; N. Takahashi; T. Konno; S. Ueda; T. Chiba; T. Shimizu; Y. Okada; S. Morishima (The Journal of Membrane Biology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

The Characteristics and Mechanisms of Uptake of PLGA Nanoparticles in Rabbit Conjunctival Epithelial Cell Layers - Mohamed G. Qaddoumi; Hideo Ueda; Johnny Yang; Jasmine Davda; Vinod Labhasetwar; Vincent H. L. Lee (Pharmaceutical Research, 2004)

Delimitation of the chromosomal region for a quantitative trait locus, qUVR-10, conferring resistance to ultraviolet-B radiation in rice (Oryza sativa L.) - T. Ueda; T. Sato; H. Numa; M. Yano (Theoretical and Applied Genetics, 2004)

Comparative analyses of serum vitellogenin levels in male and female Reeves' pond turtles ( Chinemys reevesii ) by an immunological assay - Y. Ueda; H. Hoshi; T. Uemura; Y. Kamata; N. Tada; M. Saka (Journal of Comparative Physiology B, 2004)

FISH-Mapping of 18S Ribosomal RNA Genes and Telomeric Sequences in the Japanese Bitterlings Rhodeus ocellatus kurumeus and Tanakia limbata (Pisces, Cyprinidae) Reveals Significant Cytogenetic Differences in Morphologically Similar Karyotypes - L. Sola; E. Gornung; H. Naoi; R. Gunji; C. Sato; K. Kawamura; R. Arai; T. Ueda (Genetica, 2003)

Development and disintegration of phragmoplasts in living cultured cells of a GFP?TUA6 transgenic Arabidopsis thaliana plant - K. Ueda; S. Sakaguchi; F. Kumagai; S. Hasezawa; H. Quader; U. Kristen (Protoplasma, 2003)

Application of odor-stimulated labeling methods of olfactory receptor neurons of sockeye salmon using agmatine - H. Iwase; S. Matsumoto; T. Shoji; H. Ueda (Fish Physiology and Biochemistry, 2003)

Changes in neurosteroid biosynthesis during sexual maturation of lacustrine sockeye salmon - S. Matsumoto; H. Yamada; M. Iwata; S. Adachi; K. Yamauchi; H. Ueda (Fish Physiology and Biochemistry, 2003)

Changes in GnRH levels in the brain and pituitary gland during migrations of sockeye salmon and chum salmon - T. Kitani; S. Matsumoto; H. Yamada; M. Amano; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2003)

Amino acids in stream water are essential for salmon homing migration - T. Shoji; Y. Yamamoto; D. Nishikawa; K. Kurihara; H. Ueda (Fish Physiology and Biochemistry, 2003)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Seasonal changes of hormones and muscle enzymes in adult lacustrine masu (Oncorhynchus masou) and sockeye salmon (O. nerka) - J.B.K. Leonard; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2001)

Second record of Cyclopina kiraensis , a small, brackish-water cyclopoid copepod, in Japan - H. Ueda; S. Ohtsuka; Y. Seike; S. Ohtani (Limnology, 2001)

Flexibility on the karyotype evolution in bitterlings (Pisces, Cyprinidae) - T. Ueda; H. Naoi; R. Arai (Genetica, 2001)

Investigation of physicochemical form of uranium in sediment of brackish Lake Obuchi using sequential extraction procedure - S. Ueda; H. Hasegawa; T. Iyogi; H. Kawabata; K. Kondo (Limnology, 2000)

Characteristics of fluctuations in salinity and water quality in brackish Lake Obuchi - S. Ueda; H. Kawabata; H. Hasegawa; K. Kondo (Limnology, 2000)

Human cytotoxic T-lymphocyte responses specific for peptides of the wild-type Wilms' tumor gene ( WT1 ) product - Y. Oka; O. A. Elisseeva; A. Tsuboi; H. Ogawa; H. Tamaki; H. Li; Y. Oji; E. H. Kim; T. Soma; M. Asada; K. Ueda; E. Maruya; et al. (Immunogenetics, 2000)

”In vivo cryotechnique" in combination with replica immunoelectron microscopy for caveolin in smooth muscle cells - I. Takayama; N. Terada; T. Baba; H. Ueda; Y. Kato; Y. Fujii; S. Ohno (Histochemistry and Cell Biology, 1999)

Geographical variations in the trophic structure of the plankton community along a eutrophic–mesotrophic–oligotrophic transect - S. Uye; N. Iwamoto; T. Ueda; H. Tamaki; K. Nakahira (Fisheries Oceanography, 1999)
The geographical variations in trophic structure of the plankton community, as defined by total and relative carbon biomass of phytoplankton (PP), bacteria (BA), heterotrophic nanoflagellates (HNF), microzooplankton (MZ), and herbivorous (HNZ) and carnivorous net‐zooplankton (CNZ), were investigated along an inshore–offshore transect from the innermost part of Osaka Bay to the Pacific Ocean off Kii Channel, Japan, in June 1991. Based on physico‐chemical properties of the water and topographical features, the transect was divided into three trophic areas, i.e. eutrophic, mesotrophic and oligotrophic ones. The average carbon biomass of the total plankton community was highest (438 mg m −3 ) in the inshore eutrophic area, and declined steeply offshore (141 and 26.6 mg m −3 in the mesotrophic and oligotrophic areas, respectively). In the offshore oligotrophic area, the relative biomass of BA to PP and the relative biomass of small heterotrophs (i.e. BA, HNF and MZ) to the total heterotrophs were higher than in the other areas, indicating that the microbial food chain predominated. In the mesotrophic area, the biomass of HNZ (primarily copepods) was conspicuously high, even higher than that of PP, suggesting that the traditional grazing food chain prevailed. Because of this short food chain, a productive fishing ground is formed there. In the eutrophic area, the biomass of HNZ was much smaller relative to the enormous biomass of PP, indicating that a considerable amount of primary production was not utilized directly by the metazoan zooplankton. However, the relative contribution of the small heterotrophs to the total heterotrophs’ biomass was higher in this area, as in the oligotrophic area.

Slight difference in primary amino acid sequence of p17 matrix protein of HIV-1 exerts profound influence on its antigenicity - K. Taniguchi; H. Tsuchie; S. Kageyama; M. Iwasaki; T. Takagi; F. Sasao; S. Ueda; T. Kurimura (Archives of Virology, 1998)

Correlation among dominance status, metabolic rate and otolith size in masu salmon - T. Yamamoto; H. Ueda; S. Higashi (Journal of Fish Biology, 1998)
In spatial competition between individuals, neither fish sex nor body mass affected dominance status in masu salmon Oncorhynchus masou . In contrast, resting metabolic rate ( M R ) was significantly correlated with dominance status, indicating that a high metabolic rate can increase the dominance rank of juvenile salmon. Whole animal growth rate was significantly correlated with M R , but not with initial body weight. This suggests that the body size of masu salmon is not a cause, but rather a consequence, of dominance status which is closely related to M R . The increment width between otolith daily rings was also significantly correlated with M R . Thus, the size of the Otolith may indicate the degree of M R .

Dystrophin in rod spherules; submembranous dense regions facing bipolar cell processes - H. Ueda; Takeshi Baba; Nobuo Terada; Yasuko Kato; Shigeo Tsukahara; Shinichi Ohno (Histochemistry and Cell Biology, 1997)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

Generation and characterization of the human immunodeficiency virus type 1 mutants - A. Adachi; N. Ono; H. Sakai; K. Ogawa; R. Shibata; T. Kiyomasu; H. Masuike; S. Ueda (Archives of Virology, 1991)

Characterization of a temperature-sensitive mutant in the RNA polymerase PB2 subunit gene of influenza A/WSN/33 virus - K. Yamanaka; N. Ogasawara; M. Ueda; H. Yoshikawa; A. Ishihama; K. Nagata (Archives of Virology, 1990)

Cross-reactivity among cowpox, ectromelia and vaccinia viruses with monoclonal antibodies recognizing distinct antigenic determinants in A-type inclusion bodies - N. Kitamoto; S. Tanimoto; K. Hiroi; H. Miyamoto; N. Wakamiya; S. Ueda; S. Kato (Archives of Virology, 1986)

Polypeptide analysis with monoclonal antibodies of A type inclusion bodies induced by cowpox virus - N. Kitamoto; S. Tanimoto; K. Hiroi; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1986)

Cross-reactivity between cowpox and vaccinia viruses with monoclonal antibodies - N. Kitamoto; E. Goto; S. Tanimoto; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1984)